INOVASI APLIKASI TELUNJUK SAKTI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN WONOGIRI - Dirias Ayu Prasetyani; Retno Sunu Astuti; Amni Zarkasyi Rahman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Telunjuk Sakti Application is an innovation launched by Department of Population and Civil Registration of Wonogiri Regency to overcome problems of population administrative service. Mobile based Telunjuk Sakti Application Innovation is flexibly accessible by smartphone. This research aims to analyze the acceptance responses of Telunjuk Sakti Application Innovation. Referring to the Unified Theory of Acceptance Use of Technology 2 by Venkatesh (2003), technology acceptance is analyzed using perceived usefulness, perceived ease-ofuse, relative advantage, and compliance indicators. Acceptance’s driving and inhabiting factors of Telunjuk Sakti Application Innovation is analysed using indicators constructed of many theories like risk-averse culture, facing risks inability, and innovation value suitability. This research was conducted using the qualitative descriptive method, with the subject taken by purposive sampling, locals who have been using Telunjuk Sakti Application Innovation. The results of this research, fulfillment of speed and certainty of service, service results conformity, and increased service quality, prove the fulfillment of the perceived usefulness indicator of the Telunjuk Sakti Application. The ease-of-use indicator of the service menu and the acquisition of document results have been fulfilled, but some users still encounter obstacles in the form of signal and network difficulties. On the relative advantage indicator, the benefits of convenience of use compared to manual counters, cost advantages, and time advantages have been fulfilled. Subjects and motivations for using the innovation are known, but the indicators for the sustainability of use have not been met due to network constraints. The driving factors are there is no resistance to trying technology and no technological risks to innovation. Value compliance of the innovation encourages acceptance of innovation because of the benefits offered by Telunjuk Sakti Application Innovation. The inhibiting factor of accepting innovation lies in the inability to deal with risks and changes due to network barriers that have not been fully resolved